RUANG LINGKUP PENDIDIKAN AGAMA ISLAM DALAM KONTEKS KURIKULUM MERDEKA : INTEGRASI NILAI KEAGAMAAN DALAM KEHIDUPAN SEHARI HARI - Sinta Dewi (CV. ADIBA AISHA AMIRA, 2026)
Islamic Religious Education (PAI) in the Merdeka Curriculum emphasizes not only the mastery of knowledge but also the development of character and the practical implementation of Islamic values in daily life. This study aims to examine the scope of PAI, which includes strengthening faith and worship, developing morals and character, and applying Islamic values in everyday activities. The research uses a descriptive-qualitative literature review approach, analyzing various sources related to the Merdeka Curriculum and religious education practices. The results show that strengthening faith and worship forms the spiritual foundation of students, character building instills honesty, discipline, and responsibility, while the application of Islamic values in daily life ensures that religious teachings are reflected in behavior. In conclusion, PAI in the Merdeka Curriculum plays a crucial role in forming students who are intellectually capable, morally upright, and able to consistently integrate Islamic values in personal, social, and environmental life.